Desain Pembelajaran Matematika Integrasi QS. Al-Baqarah: 261 Melalui Constructivism and Sociocultural Learning pada Materi Persentase, Barisan dan Deret - Ziska Olivia Abdul Gani; Lulu'un Najwa; Tasamaratul Janiah; Nina Ramadhani Hidayah; Nabila Haerunnisah; Susilawati; Olivia; Dina Ekawati; M. Gunawan Supiarmo; Junaidi (Griya Journal of Mathematics Education and Application, 2024)
This research aims to explore the mathematical concepts contained in the verse Q.S Al-Baqarah: 261 and design a learning design that integrates the mathematical values of this verse. Verse 261 of Surah Al-Baqarah describes a metaphor that connects the value of charity with growth and abundant results, which can be linked to mathematical concepts such as percentages, rows, and series of numbers. This research employs an interdisciplinary approach to explore how junior high school students can transform their understanding of mathematical concepts from the Al-Qur'an into a relevant and enjoyable learning experience. This type of research is qualitative research with a development studies type design research approach. The proposed learning design integrates existing moral values and mathematical concepts using Constructivism and socio-cultural learning. It is hoped that through this integrated learning, students can develop a deeper understanding of mathematics, especially percentages, ranks, and series, as well as increase their awareness of the importance of charity and social contributions. This research contributes to the development of learning that combines religious values with mathematics learning